A Class of d-Dimensional Dirac Operators with a Variable Mass. (1st July 2013) - Arai, Asao; Dagva, Dayantsolmon
Abstract : A class of d -dimensional Dirac operators with a variable mass is introduced (d ≥ 2 ), which includes, as a special case, the 3-dimensional Dirac operator describing the chiral quark soliton model in nuclear physics, and some aspects of it are investigated.